Conducta suicida en el hospital general - Tapia I., Patricia; Vohringer C., Paul; Ornstein L., Claudia (Revista Hospital Clínico Universidad de Chile, 2010)
The authors analize the current characteristics of suicidal behaviour. They also propose, throught the article, an Intervention Protocol that could be used at the emergency Service of the Clinical Hospital of U. de Chile.